A Medieval Ships Crew and their Weapon: from Archaeological Material to Interpretations - Valentyrova, Kateryna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Comprehensive research of artefacts has become the norm for modern archaeology. Archaeologist must pay attention to all aspects of the investigating problem and analyze material by means of methods from different branches of science. The Center for Underwater Archaeology of Taras Shevchenko National University of Kyiv have been researching finds from a medieval Italian shipwreck since 1999, with a very interesting group of artefacts consisting of baselard type daggers. At the stage of interpretation, we decided to use methods which are characteristic of historical science, with a reconstruction of medieval people’s` perceptions of baselards forming the basis for it. The combination of data about the material object itself and its image (the concept of it) turned out to be useful for ensuring a clear interpretation of archaeological finds and even for the verification of some social reconstructions.
Keywords: baselard; medieval trade galley; personal belongings; perception; comprehensive research